Binding Mode, Absorption, And Distribution Profile, Mutagenicity and Carcinogenicity of Asam Gelugur (Garcinia atroviridis Griff.) Fruit Phytoconstituents as Influenza H7N9 Neuraminidase Inhibitor - Mohamad Taufik Ismullah; Sri Adi Sumiwi; Tiana Milanda; Muchtaridi Muchtaridi (Indonesian Journal of Pharmaceutical Science and Technology, 2019)
The purpose of this study was to predict the bond mode, absorption and distribution profile as well as the mutagenicity and carcinogenicity of the asam gelugur fruit compounds which have the best inhibitory activity in neuraminidase influenza subtype H7N9 active pocket by in silico. Pharmacophore modeling and molecular docking using Ligandscout software. Absorption and distribution profiles using PreADMET software. Mutagenicity and carcinogenicity using Toxtree software. The results showed that 10 of the 13 compounds of asam gelugur fruit formed hydrogen bonds with important amino acid residues in the active sac neuraminidase H7N9. Organic acid group compounds have good absorption and distribution profiles. All acid gelugur fruit compounds are predicted not to be mutagenic and carcinogenic. Hydroxycitric acid is a compound that is predicted to have the best inhibition with the lowest Ki value of 1.09 µM. Hydroxycitric acid is a compound that is predicted to have the best inhibition with the lowest Ki value of 1.09 µM.Keywords: Neuraminidase Inhibitor, Influenza, H7N9, Hydroxycitric Acid